فاعلية برنامج قائم على فن الميم (التمثيل الصامت) لزيادة نسبة تركيز طفل الروضة المصاب باضطراب زيادة الحركة وتشتت الانتباه - جنيدي، جيهان ماهر طه; النقيب، أسماء فتحي أيوب خضر; الأمين، طاهرة حسن عبدالله (دار سمات للدراسات والأبحاث, 2017)
This study aims to reveal the effectiveness of a program based on (mime) art to increase the focus ratio of kindergarten children Infected by Attention Deficit Hyperactivity. To achieve the objectives of the study the following tools were used Questionnaire Note codified for the attention deficit –hyperactivity, This contributes in a sample selection, which was 30 children, - attention deficit -hyperactivity disorder scale tool. It contributes to measure the degree of attention deficit -hyperactivity disorder for kindergarten children before and after the application of( Mime) art program.( Mime) art program. we applied (Mime) art program on 30 boys and girls in public kindergartens in skaka presenting some life situations , child's stories and puzzles by a silent acting By governmental kindergartens children of Al-Jouf Skaka. study used quasi-experimental approach and the descriptive approach. Data were collected for attention deficit –hyperactivity disorder scale for the kindergarten children before and after applying the program. statistical programs were applied, analyzing the results and validate the assumptions and discuss the results and the results proved the existence of statistically significant differences between the experimental group differences before and after the application of the program for the benefit of post-test shows The effectiveness of a program based on (mime) art to increase the focus ratio of kindergarten children Infected by Attention Deficit Hyperactivity.
هدفت الدراسة إلى الكشف عن فاعلية برنامج قائم على فن الميم (التمثيل الصامت) علي زيادة نسبة تركيز طفل الروضة المصاب بزيادة الحركة وتشتت الانتباه. ولتحقيق أهداف الدراسة تم استخدام استبانة ملاحظة مقننة لاضطراب زيادة الحركة وتشتت الانتباه طبق من خلال معلمة الفصل عن طريق ملاحظة الأطفال لمدة أسبوع كامل ومقياس زيادة الحركة وتشتت الانتباه لطفل الروضة يطبق من خلال متخصصين في التربية وعلم النفس ورياض الأطفال ويطبق قبل برنامج الميم (التمثيل الصامت) وبعده على الأطفال الحاصلين علي اكثر من 40 % علي مقياس زيادة الحركة وتشتت الانتباه وبرنامج فن الميم الذي يعتمد على بعض المواقف الحياتية لطفل الروضة وبعض الألغاز وبعض القصص القصيرة اعتمدت الدراسة علي المنهج شبه التجريبي والمنهج الوصفي وقد طبق برنامج فن الميم (التمثيل الصامت) على 30 طفلا وطفلة في الروضات الحكومية بسكاكا بعرض بعض المواقف الحياتية في بيئة الطفل والألغاز والقصص الصامتة. وتم عرض بعض المواقف الحياتية والألغاز والقصص الصامتة باستخدام فن الميم (التمثيل الصامت) لأطفال الروضات الحكومية بالجوف سكاكا تم جمع البيانات زيادة الحركة وتشتت الانتباه لطفل الروضة قبل تطبيق البرنامج وبعده وطبقت البرامج الإحصائية وتم تحليل النتائج. أثبتت النتائج وجود فروق ذات دلالة إحصائية بين المجموعة التجريبية قبل وبعد تطبيق البرنامج لصالح الاختبار البعدي، مما يدل علي فاعلية البرنامج القائم علي فن الميم (التمثيل الصامت) لزيادة نسبة تركيز طفل الروضة المصاب باضطراب زيادة الحركة وتشتت الانتباه.
Keywords: التمثيل الصامت ( الميم ) -- اضطراب زيادة الحركة وتشتت الانتباه -- نسبة تركيز طفل الروضة